The performative pleasure of imprecision: a diachronic study of entrainment in music performance - Geeves, Andrew; McIlwain, Doris J.; Sutton, John (Frontiers in Human Neuroscience, 2014)
This study focuses in on a moment of live performance in which the entrainment amongst a musical quartet is threatened. Entrainment is asymmetric in so far as there is an ensemble leader who improvises and expands the structure of a last chorus of a piece of music beyond the limits tacitly negotiated during prior rehearsals and performances. Despite the risk of entrainment being disturbed and performance interrupted, the other three musicians in the quartet follow the leading performer and smoothly transition into unprecedented performance territory. We use this moment of live performance to work back through the fieldwork data, building a diachronic study of the development and bases of entrainment in live music performance. We introduce the concept of entrainment and profile previous theory and research relevant to entrainment in music performance. After outlining our methodology, we trace the evolution of the structure of the piece of music from first rehearsal to final performance. Using video clip analysis, interviews and field notes we consider how entrainment shaped and was shaped by the moment of performance in focus. The sense of trust between quartet musicians is established through entrainment processes, is consolidated via smooth adaptation to the threats of disruption. Nonverbal communicative exchanges, via eye contact, gesture and spatial proximity, sustain entrainment through phase shifts occurring swiftly and on the fly in performance contexts. These exchanges permit smooth adaptation promoting trust. This frees the quartet members to play with the potential disturbance of equilibrium inherent in entrained relationships and to play with this tension in an improvisatory way that enhances audience engagement and the live quality of performance.